2009
DOI: 10.1039/b817881j
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of copper composites from deep eutectic solvents based on choline chloride

Abstract: Here we describe for the first time the electrolytic deposition of copper and copper composites from a solution of the metal chloride salt in either urea-choline chloride, or ethylene glycol-choline chloride based eutectics. We show that the deposition kinetics and thermodynamics are quite unlike those in aqueous solution under comparable conditions and that the copper ion complexation is also different. The mechanism of copper nucleation is studied using chronoamperometry and it is shown that progressive nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
265
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(298 citation statements)
references
References 38 publications
22
265
2
3
Order By: Relevance
“…35,42 The observed electrochemical behaviour for AuCl in Ethaline 200 is also similar to that observed for the Ag +/0 and Cu +/0 redox couples, with well-defined, chemically reversible deposition and stripping behaviour. 38,43,44 Multiple peaks are visible in the FT for the KAu(CN) 2 solution, Figure 3 (c), suggesting coordination with two cyanide ligands. This speciation is also observed for KAu(CN) 2 in both aqueous and quaternary ammonium salt solutions.…”
Section: Speciationmentioning
confidence: 99%
“…35,42 The observed electrochemical behaviour for AuCl in Ethaline 200 is also similar to that observed for the Ag +/0 and Cu +/0 redox couples, with well-defined, chemically reversible deposition and stripping behaviour. 38,43,44 Multiple peaks are visible in the FT for the KAu(CN) 2 solution, Figure 3 (c), suggesting coordination with two cyanide ligands. This speciation is also observed for KAu(CN) 2 in both aqueous and quaternary ammonium salt solutions.…”
Section: Speciationmentioning
confidence: 99%
“…These 'type-III' DES systems have been used to deposit a wide range of metals including Al, Zn, Fe, Ni, Sn, Cr, Al and Cu [2][3][4][5][6][7] . Studies [8][9][10][11][12][13][14] of copper deposition have been particularly common as it is used extensively in the electronics and microelectronic industries and can be regarded as a model system. Additionally there is a large body of existing studies of 4 Cu deposition from conventional ILs and aqueous systems which can be used to benchmark DES-based processes.…”
Section: In 2003mentioning
confidence: 99%
“…Owing to their physical properties, many researchers have reported that DESs have feasible industrial applications [18][19][20][21][22][23]. As reviewed by Zhang et al, [24] and Tang et al, [25], there are many potential areas to which DESs can be applied.…”
Section: Less Hazardous Constituents and Productsmentioning
confidence: 99%